2019
DOI: 10.22219/jrak.v9i2.8902
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Good Corporate Governance, Financial Performance and Sustainability Report

Abstract: This study aims to analysiss and examine the effect of the financial performance and good corporate governance on sustainability report. Financial performance is measured using ROA. Good corporate governance mechanisms used are managerial ownership, independent commissioner board, board of directors and independent audit committee. The population is state-owned companies listed in the Indonesia Stock Exchange during 2011-2014. A purposive sampling method is used as a sampling method and 13 companies are select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 1 publication
2
14
2
15
Order By: Relevance
“…Besides, the total number of companies that disclosed sustainability reports during the pandemic also decreased. The results of the study are not in line with Justin and Hadiprajitno (2019), Latifah et al (2019), andMudiyanselage (2018), which stated that board size had a positive effect on design. Meanwhile, the results of this study align with research conducted by Fuente et al (2017), which did not confirm the relationship between board size and performance.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Besides, the total number of companies that disclosed sustainability reports during the pandemic also decreased. The results of the study are not in line with Justin and Hadiprajitno (2019), Latifah et al (2019), andMudiyanselage (2018), which stated that board size had a positive effect on design. Meanwhile, the results of this study align with research conducted by Fuente et al (2017), which did not confirm the relationship between board size and performance.…”
Section: Resultscontrasting
confidence: 80%
“…In addition, Katmon et al (2017) found that the educational diversity of the board of directors had a positive effect on disclosure, while Khan et al (2019) stated that the diversity of the board of directors' education did not affect disclosure. Besides, the studies on the size of the board of directors have been carried out by Justin and Hadiprajitno (2019), Latifah et al (2019), andMudiyanselage (2018), who uncovered that the size of the board of directors had a positive effect on disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Komite Audit yang berintegritas akan mampu memahami makna strategis dari pengungkapan sustainability report sebagai alat komunikasi perusahaan dengan pemangku kepentingannya. Semakin efektif Komite Audit menjalankan tugasnya akan diikuti semakin berkualitasnya sustainability report perusahaan (Latifah et al, 2019;Natalia et al, 2016). H6: Komite Audit berpengaruh positif signifikan terhadap kualitas sustainability report.…”
Section: Pengaruh Komite Audit Terhadap Kualitas Sustainability Reportunclassified
“…Penelitian lainnya mengenai laporan keberlanjutan yang juga banyak dilakukan yaitu mengeksplorasi faktor-faktor yang dapat mempengaruhi pengungkapan laporan keberlanjutan itu sendiri, seperti penelitian yang telah dilakukan oleh (Afifulhaq, 2018) dengan melihat pengaruh profitabilitas, likuiditas, leverage, aktivitas perusahaan, dan tata kelola perusahaan terhadap pengungkapan laporan keberlanjutan. Penelitian serupa juga telah dilakukan oleh (Aliniar & Wahyuni, 2017), (Rahman, 2017), (Diono & Prabowo, 2017), (Safitri & Saifudin, 2019), (Dissanayake et al, 2019), (Latifah et al, 2019), (Chang et al, 2019), (Masum et al, 2020), (Amidjaya & Widagdo, 2020), (Febriyanti, 2021) dan (Tanjung, 2021) dengan menggunakan beberapa variabel seperti kinerja keuangan, profitabilitas, budaya, Good Corporate Governance, karakteristik dari dewan, dan karakteristik dari perusahaan sebagai variabel independen yang mempengaruhi pengungkapan laporan keberlanjutan.…”
Section: Pendahuluanunclassified